BERCERITA DENGAN GAMBAR UNTUK MENINGKATKAN KOSAKATA ANAK USIA DINI - Yohana, Miming; Indiati, Indiati; Laeli, Khusnul (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2013)
The purposes of this research is to determine the child’s vocabulary enhancement through storytelling with pictures in kindergarten Mardisiwi Seborokrapyak Banyuurip District of Purworejo. The methods of the research was conducted by Action Research (PTK), which was implemented to enhance the child’s vocabulary through storytelling with pictures. The research was conducted on children in kindergartens Mardisiwi Seborokrapyak Banyuurip District of Purworejo to 12 research subjects consisting of 5 boys and 7 girls. In this research tells the story with pictures included in the activities. This research uses three variables: input variables, process variables, output variables. The use of performance data collection is by using and coordinating research data obtained by the research criteria and indicators of success set at 75%.The conclusion of this research is the vocabulary skills of kindergarten children Mardisiwi Seborokrapyak Banyuurip District of Purworejo can be increased after learning storytelling with pictures. This is proven by the results of the changes in each cycle, while the average initial capability child’s vocabulary originally 49.5%, after the first cycle measures the average vocabulary skills of children increased to 61.5%, and after the second cycle of vocabulary skills children increased to 91.1%. Hypothesis storytelling with images effectively improve vocabulary at kindergarten children Mardisiwi Seborokrapyak Banyuurip District of Purworejo proven true.